Analysis Of Factors Associated The Occurrence Of Acute Resipiratory Tract Infection (ARI) In Toddlers In Working Area Sukamerindu Health Center, Bengkulu City In 2021 - Maharani, Fera Sepi Handaryanti; Fauzi, Yusran; Wulandari, Wulandari; Samidah, Ida; Darmawansyah, Darmawansyah (Journal Hygeia Public Health, 2024)
Intoduction: ARI disease is still one of the important public health problems to be considered because it is an acute disease and can even cause death. Data obtained from the ARI Poly at the Sukamerindu Health Center, Bengkulu City, in the last 3 years has always experienced the highest ARI cases in Bnegkulu City, in 2020 there were 354 cases. The purpose of this study was to analyze the factors associated with the incidence of ARI in toddlers in the Working Area of the Sukamerindu Health Center, Bengkulu city in 2021. Method: This type of research is quantitative with a cross sectional research design. The sample amounted to 100 respondents with simple random sampling technique. The instrument used was a questionnaire sheet. Data analysis was performed univariate and bivariate (using chi square test with α=0.05) using SPSS 16 software. Result and Discussion: The results showed that more than half of the respondents had smoking habits of family members, more than half of the respondents had residential density, more than half of the respondents had LBW, more than half of the respondents experienced ARI at the Sukamerindu Health Center, Bengkulu City in 2021. Based on the bivariate analysis, it is known that there is a significant relationship between the smoking habits of family members and the incidence of ARI, there is a significant relationship between occupancy density and the incidence of ARI and there is a significant relationship between LBW and the incidence of ARI at the Sukamerindu Health Center, Bengkulu City, 2021. Conclusion: It is expected that health workers at the Sukamerindu Health Center continue to carry out health promotion measures in the form of education to increase knowledge about what risk factors can cause ARI and how to prevent it.